Method for doubly modifying electrolyte material based on fluorine element and electrolyte material prepared by method
By performing double modification of the ceramic electrolyte in lithium-ion batteries based on fluorine elements, the problems of dendrites growth and interface instability are solved, and the cycle stability and service life of the battery are significantly improved.
Patent Information
- Application Number
- CN202411939897.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-28
AI Technical Summary
Due to problems such as dendrite growth, interface instability and stress strain, lithium-ion batteries have deteriorated cycle performance and capacity attenuation, hindering the development of high energy density and high safety batteries.
The double modification method based on fluorine elements is adopted to modify the ceramic electrolyte body and the interface layer respectively, and the mechanical properties and interface stability of the ceramic electrolyte are improved by adding fluorine-containing compounds.
It significantly improves the long cycle stability of ceramic electrolytes, inhibits dendrites' growth, improves interface wetting and overall stability of the battery, and extends the service life of the battery.
Smart Images

Figure CN119707435A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of electrochemistry, and in particular relates to a method for doubly modifying an electrolyte material based on fluorine element and an electrolyte material prepared by the method. Background Art
[0002] At present, energy issues have become a major problem for the progress of human society, and the research and development of clean and sustainable energy is a very important topic at present. Compared with traditional liquid electrolytes, ceramic electrolytes have the following advantages over liquid electrolytes: higher safety, ceramic electrolytes have a higher melting point and stability, which can avoid safety hazards such as leakage and explosion of liquid electrolytes; longer service life, ceramic electrolytes have a longer service life than liquid electrolytes, which can reduce the frequency and cost of replacing electrolytes; higher energy density, ceramic electrolytes have higher ion conductivity, can support higher charge density and energy density, thereby improving battery performance; stronger temperature resistance, the high melting point and high thermal stability of ceramic electrolytes enable them to withstand higher operating temperatures, making them suitable for more application scenarios.
[0003] The inherent defects of lithium-ion batteries can lead to internal growth of dendrites, poor solid-solid contact with the negative electrode alkali metal, poor wettability with the positive electrode, and stress-strain behavior of the electrode during the cycle, all of which will cause interface side reactions, deteriorate battery cycle performance, and accelerate capacity decay. These problems have seriously hindered the development and practical application of high-energy-density and high-safety lithium-ion batteries.
[0004] At present, advanced surface coating technologies such as magnetron sputtering, atomic layer deposition, and vapor deposition have been successfully applied to modified ceramic electrolytes, which have a certain effect on improving the performance of ceramic electrolytes and battery cycle stability. However, due to factors such as equipment technology, it is not yet possible to apply them on a large scale.
[0005] In order to solve the above problems, the present invention is proposed. Summary of the invention
[0006] In response to the existing technology's requirements for bulk modification and interface modification of ceramic electrolytes, the present invention provides a method for dual-modified electrolyte materials based on fluorine elements so that it can be widely used in the field of high-energy-density and high-safety lithium-ion batteries.
[0007] To achieve this technical purpose, the scheme of the present invention is:
[0008] The first aspect of the present invention provides a method for double-modified electrolyte materials based on fluorine elements, which comprises: using fluorine-containing compounds to modify the ceramic electrolyte body and the ceramic electrolyte interface layer with fluorine elements respectively, so that the ceramic electrolyte body and the ceramic electrolyte interface layer are both added with fluorine-containing compounds, thereby double-modified electrolyte materials based on fluorine elements, wherein the melting point of the fluorine-containing compound is lower than the sintering temperature of the ceramic electrolyte. The ceramic electrolyte interface layer contains fluorine and the ceramic electrolyte body contains fluorine to double-modify the ceramic electrolyte inside and outside.
[0009] Preferably, the method of modifying the ceramic electrolyte body with fluorine element by using a fluorine-containing compound comprises: adding the fluorine-containing compound to the ceramic electrolyte body to obtain a fluorine-containing ceramic electrolyte body, thereby completing the modification of the ceramic electrolyte body;
[0010] The method of using fluorine-containing compounds to modify the ceramic electrolyte interface layer with fluorine elements includes: immersing the ceramic electrolyte in a glass bottle filled with a polymer protective layer added with fluorine-containing compounds, so that the ceramic electrolyte is in uniform and sufficient contact with the polymer protective layer added with fluorine-containing compounds, forming a fluorine-containing polymer protective layer on the surface of the ceramic electrolyte, and completing the modification of the ceramic electrolyte interface layer.
[0011] Preferably, the fluorine-containing compound includes a fluorine-containing inorganic compound and / or a fluorine-containing polymer and / or a fluorine-containing organic compound, and the fluorine-containing compound includes one or more of lithium fluoride, calcium fluoride, aluminum fluoride, barium fluorosilicate, sodium fluoride, polyvinylidene fluoride, polytetrafluoroethylene, fluorine-containing polyimide, polyperfluoroethylene, polychlorotrifluoroethylene or lithium bis(trifluoromethylsulfonyl)imide.
[0012] Preferably, the melting point of the fluorine-containing inorganic compound is lower than 900°C; and the melting point of the fluorine-containing polymer is lower than 500°C.
[0013] Preferably, the amount of the fluorine-containing compound added to the fluorine-containing ceramic electrolyte body is 1wt%-6wt% of the ceramic electrolyte body, and the amount of the fluorine-containing compound added to the fluorine-containing polymer protective layer is 1wt%-2wt% of the polymer protective layer (polymer matrix).
[0014] Preferably, the polymer protective layer to which the fluorine-containing compound is added needs to be in liquid state, and the heating temperature is 80°C-140°C.
[0015] Preferably, the polymer protective layer is based on succinonitrile and has a lithium salt content of not less than 1 wt %.
[0016] Preferably, the ceramic electrolyte is immersed in the container containing the polymer protective layer to which the fluorine-containing compound is added for 1-5 minutes.
[0017] Preferably, the ceramic electrolyte is an inorganic ceramic electrolyte.
[0018] Preferably, the double-modified electrolyte material based on fluorine element is used to improve the cycle stability of the electrolyte material and avoid short circuit of the electrolyte material.
[0019] The second aspect of the present invention provides a lithium ion battery, wherein the ceramic electrolyte body and the ceramic electrolyte interface layer are fluorine-containing ceramic electrolyte body and fluorine-containing polymer protective layer prepared by the method of double-modified electrolyte material based on fluorine element described in the first aspect of the present invention.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] 1. The method of the double modified electrolyte material based on fluorine element provided by the present invention, in the first aspect, the fluorine element doped inorganic ceramic electrolyte body greatly improves the mechanical properties of the inorganic electrolyte body, enhances the effect of dispersing stress, inhibits the growth of dendrites, and effectively improves the long cycle stability of the electrolyte material. In the second aspect, the polymer protective layer matrix to which the fluorine-containing compound is added is heated, and the electrolyte sheet is evenly immersed for 1-5 minutes, and a uniform fluorine-containing polymer protective layer is formed on the surface, which improves the contact between the positive and negative electrodes and the inorganic ceramic electrolyte, improves the interface stability, and inhibits the growth of lithium dendrites. In addition, the fluorine-containing polymer protective layer improves the wettability of the interface, and the positive electrode releases more capacity, improving the cycle stability of the battery. The method of the double modified electrolyte material based on fluorine element provided by the present invention, the body modified inorganic ceramic electrolyte cooperates with the fluorine-containing modified polymer protective layer, and the double modification jointly promotes the long cycle stability of the battery.
[0022] 2. In the method of double-modified electrolyte materials based on fluorine element provided by the present invention, the polymer protective layer can effectively reduce the side reaction between the inorganic ceramic electrolyte and the lithium sheet, inhibit the growth of dendrites, and achieve the purpose of avoiding battery short circuit.
[0023] 3. In the method of double-modified electrolyte materials based on fluorine element provided by the present invention, there is a synergistic and progressive relationship between the modification of the ceramic electrolyte body and the modification of the ceramic electrolyte interface layer. The modification of the ceramic electrolyte body uses the fluorine element to connect the modification of the ceramic electrolyte interface layer in series, and the fluorinated film generated by the cycle of the two will be stronger. The fluorinated layer generated during the ceramic electrolyte cycle is bonded to the polymer protective layer at the molecular or even atomic level, thereby greatly improving the stability of the modified layer and the stability of the entire battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a surface SEM image of the unmodified LATP provided in Example 1 of the present invention;
[0025] Figure 2 This is a surface SEM image of the modified LATP provided in Example 1 of the present invention;
[0026] Figure 3 The unmodified Li / SN / LATP / SN / LATP symmetric battery provided in Example 1 of the present invention has a conductivity of 0.4 mA cm -2 Constant current cycle diagram under current density;
[0027] Figure 4 The modified Li / SN / LATP / SN / LATP symmetric battery provided in Example 1 of the present invention has a conductivity of 0.4 mA cm -2 Constant current cycle diagram under current density;
[0028] Figure 5 This is a battery capacity diagram of the unmodified Li / SN / LATP / SN / LFP full battery provided in Example 2 of the present invention at 0.1c;
[0029] Figure 6 This is a battery capacity diagram of the modified Li / SN / LATP / SN / LFP full battery provided in Example 2 of the present invention at 0.1c. DETAILED DESCRIPTION
[0030] The present invention is further described below by way of examples, which are not limited to the examples. Experimental methods without specific conditions specified in the examples are generally carried out under conventional conditions and conditions described in the manual, or under conditions recommended by the manufacturer. The general equipment, materials, reagents, etc. used are all commercially available unless otherwise specified.
[0031] In order to further illustrate the method of the fluorine-based dual-modified electrolyte material provided by the present invention, it is described in detail below with reference to examples.
[0032] Embodiment 1:
[0033] A method for double-modified electrolyte materials based on fluorine elements, wherein the modified ceramic electrolyte is a NASICON Li superion conductor LATP (lithium aluminum titanium phosphate) ceramic sheet, the fluorine-containing compound added to the ceramic electrolyte body is lithium fluoride LiF, the negative electrode is metallic lithium, and the polymer protective layer is a polymer matrix (succinonitrile) plus an appropriate amount of fluorine-containing compounds (lithium bistrifluoromethylsulfonyl imide (LiTFSI) and lithium fluoride (LiF)). The preparation and assembly of the electrode materials of the battery are carried out under an inert atmosphere (argon). The amount of fluorine-containing compounds added to the fluorine-containing ceramic electrolyte body is 4 wt% of the ceramic electrolyte body, and the amount of fluorine-containing compounds added to the fluorine-containing polymer protective layer is 1.5 wt% of the polymer matrix.
[0034] Step (1), first prepare a body-modified inorganic ceramic electrolyte, take the required raw materials lithium carbonate, lithium fluoride, ammonium dihydrogen phosphate and aluminum oxide according to the chemical LATP stoichiometric ratio, then ball mill, dry, sieve, obtain raw material powder, then pre-sinter at 600 ° C, mix evenly, manually grind the calcined precursor, sieve it into powder, ball mill, dry, sieve to obtain a powder with uniform particles. Put the obtained powder into a mold and isostatically press it at 200MPa. The holding time is 120min, and an electrolyte disc with a diameter of 11mm and a thickness of 1.6mm is prepared.
[0035] Step (2), then modify the ceramic electrolyte interface layer with fluorine, polish and grind the smooth ceramic sheet, assemble the battery in a glove box, heat to 80°C to make the polymer protective layer liquid, then soak the ceramic sheet in it for 1-3 minutes, press the cut lithium sheet (8 mm in diameter, 300 μm in thickness) onto the protective layers on both sides, and let it stand for five minutes to obtain Li / SN / LATP / SN / Li.
[0036] For comparison, this embodiment prepares an unmodified LATP ceramic electrolyte, where unmodified means that during the preparation of the LATP ceramic electrolyte body in step (1), lithium fluoride is not added, fluorine element modification is not performed, and step (2) of modifying the ceramic electrolyte interface layer with fluorine element is not performed.
[0037] Specifically, Figure 1 This is a scanning electron microscope diagram of the LATP ceramic electrolyte before modification; Figure 2 Figure 1 is a schematic diagram of the SEM of the modified LATP. It can be seen from the figure that the internal structure of the modified LATP is more compact and no obvious pores appear. Figure 3 The symmetric cell with unmodified LATP ceramic electrolyte at 0.05 mA cm -2 Constant current cycle diagram under current density; Figure 4 The LiF-doped LATP symmetric battery has a charge transfer capacity of 0.05 mA cm -2 The constant current cycle diagram under current density shows that the modified LATP has higher cycle stability.
[0038] Embodiment 2:
[0039] A method for double-modified electrolyte materials based on fluorine elements, wherein the modified ceramic electrolyte is a NASICON Li superion conductor LAGP (lithium aluminum germanium phosphate) ceramic sheet, the fluorine-containing compound added to the ceramic electrolyte body is LiF, the negative electrode is metallic lithium, and the polymer protective layer is a polymer matrix (succinonitrile) plus an appropriate amount of fluorine-containing compounds (lithium bistrifluoromethylsulfonyl imide (LiTFSI) and lithium fluoride (LiF)). The preparation and assembly of the electrode materials of the battery are carried out under an inert atmosphere (argon). The amount of fluorine-containing compounds added to the fluorine-containing ceramic electrolyte body is 6wt% of the ceramic electrolyte body, and the amount of fluorine-containing compounds added to the fluorine-containing polymer protective layer is 2wt% of the polymer matrix.
[0040] Step (1), first prepare a body-modified inorganic ceramic electrolyte, take the required raw materials lithium carbonate, lithium fluoride, ammonium dihydrogen phosphate and aluminum oxide according to the chemical LAGP stoichiometric ratio, then ball mill, dry, sieve to obtain raw material powder, then pre-sinter at 600°C, mix evenly, manually grind the calcined precursor, sieve it into powder, ball mill, dry, sieve to obtain a powder with uniform particles. Put the obtained powder into a mold and isostatically press it at 200MPa. The holding time is 120min, and an electrolyte disc with a diameter of 11mm and a thickness of 1.6mm is prepared.
[0041] Step (2), then modify the ceramic electrolyte interface layer with fluorine, polish and grind the smooth ceramic sheet, assemble the battery in a glove box, heat to 80°C to make the polymer protective layer liquid, and then soak the ceramic sheet in it for 1-3 minutes, press the cut lithium sheet (8mm diameter, 300μm thickness) on one side of the protective layer, and cut the positive electrode sheet (LFP, 2mg cm -2 ) Let it stand for five minutes to obtain Li / SN / LAGP / SN / LFP.
[0042] For comparison, this embodiment prepares an unmodified LAGP ceramic electrolyte, where unmodified means that during step (1) the preparation of the LAGP ceramic electrolyte body, no lithium fluoride is added, no fluorine element modification is performed, and step (2) the step of modifying the ceramic electrolyte interface layer with fluorine element is not performed.
[0043] Figure 5 is the battery capacity graph of unmodified LAGP cycled at 0.2c rate; Figure 6 This is the battery capacity diagram of the modified LAGP cycled at a rate of 0.2c. It is obvious that the cycle time is longer and the capacity decay is less.
[0044] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.
Claims
1. A method for double-modified electrolyte materials based on fluorine element, characterized in that: The method comprises: using fluorine-containing compounds to modify the ceramic electrolyte body and the ceramic electrolyte interface layer with fluorine elements respectively, so that the ceramic electrolyte body and the ceramic electrolyte interface layer are both added with fluorine-containing compounds, thereby doubly modifying the electrolyte material based on the fluorine element, and the melting point of the fluorine-containing compound is lower than the sintering temperature of the ceramic electrolyte.
2. The method of double-modified electrolyte material based on fluorine element according to claim 1, characterized in that: The method of modifying a ceramic electrolyte body with fluorine by using a fluorine-containing compound comprises: adding the fluorine-containing compound to the ceramic electrolyte body to obtain a fluorine-containing ceramic electrolyte body, thereby completing the modification of the ceramic electrolyte body; The method of using fluorine-containing compounds to modify the ceramic electrolyte interface layer with fluorine elements includes: immersing the ceramic electrolyte in a container filled with a polymer protective layer added with fluorine-containing compounds, allowing the ceramic electrolyte to contact the polymer protective layer added with fluorine-containing compounds, forming a fluorine-containing polymer protective layer on the surface of the ceramic electrolyte, and completing the modification of the ceramic electrolyte interface layer.
3. The method of double-modified electrolyte material based on fluorine element according to claim 2, characterized in that: The fluorine-containing compound includes a fluorine-containing inorganic compound and / or a fluorine-containing polymer and / or a fluorine-containing organic compound, and the fluorine-containing compound includes one or more of lithium fluoride, calcium fluoride, aluminum fluoride, barium fluorosilicate, sodium fluoride, polyvinylidene fluoride, polytetrafluoroethylene, fluorine-containing polyimide, polyperfluoroethylene, polychlorotrifluoroethylene or lithium bis(trifluoromethylsulfonyl)imide.
4. The method of double-modified electrolyte material based on fluorine element according to claim 3, characterized in that: The melting point of the fluorine-containing inorganic compound is lower than 900°C; the melting point of the fluorine-containing polymer is lower than 500°C.
5. The method of double-modified electrolyte material based on fluorine element according to claim 2, characterized in that: The amount of the fluorine-containing compound added to the fluorine-containing ceramic electrolyte body is 1wt%-6wt% of the ceramic electrolyte body, and the amount of the fluorine-containing compound added to the fluorine-containing polymer protective layer is 1wt%-2wt% of the polymer protective layer.
6. The method of double-modified electrolyte material based on fluorine element according to claim 2, characterized in that: The polymer protective layer with fluorinated compounds added needs to be in liquid state, and the heating temperature is 80℃-140℃; The polymer protective layer is based on succinonitrile, and the lithium salt content is not less than 1wt%.
7. The method of double-modified electrolyte material based on fluorine element according to claim 2, characterized in that: The ceramic electrolyte is immersed in the container containing the polymer protective layer to which the fluorine-containing compound is added for 1 to 5 minutes.
8. The method of double-modified electrolyte material based on fluorine element according to claim 2, characterized in that: The ceramic electrolyte is an inorganic ceramic electrolyte.
9. The method of double-modified electrolyte material based on fluorine element according to claim 1, characterized in that: The double-modified electrolyte material based on fluorine element is used to improve the cycle stability of the electrolyte material and avoid short circuit of the electrolyte material.
10. An electrolyte material, characterized in that: The ceramic electrolyte body and the ceramic electrolyte interface layer are a fluorine-containing ceramic electrolyte body and a fluorine-containing polymer protective layer prepared by the method for preparing a fluorine-based dual-modified electrolyte material according to any one of claims 1 to 9.